English Drug Information Comprehension Among Patients with Degenerative Diseases - Ahmad Nurwanto; Muhammad Aisy Akbar Firdaus; Ika Pratiwi; Wendi .; Maulida Nabila (CV. ITTC INDONESIA, 2026)
Problem The increasing use of English in medication labels, package inserts, and pharmaceutical information resources presents challenges for patients with chronic diseases, particularly in primary healthcare settings where medication literacy is essential for safe and effective medicine use. This study aimed to assess the level of English drug information comprehension among patients with degenerative diseases attending Tirtajaya Primary Health Center. A descriptive cross-sectional study was conducted from April to June 2026 involving 135 patients selected through purposive sampling. Data were collected using a structured questionnaire assessing participants' understanding of English medication terminology, including generic drug names, dosage instructions, administration frequency, storage conditions, warning statements, and adverse effects. Descriptive statistics were used to summarize demographic characteristics and comprehension levels. Of the 135 participants, 55.6% were male and 44.4% were female, with most aged 26–35 years (39.3%). The majority had completed a bachelor's degree (44.4%) and worked as private employees (37.0%). Assessment of English drug information comprehension showed that 51.9% of participants demonstrated moderate comprehension, 37.8% achieved good comprehension, and 10.4% had poor comprehension. While most respondents understood basic medication instructions, many experienced difficulty interpreting specialized pharmaceutical terminology. Patients with degenerative diseases generally demonstrated moderate English drug information comprehension. Strengthening pharmacist-led counseling, improving medication literacy, and providing bilingual educational materials may enhance patients' understanding of medication information, promote the rational use of medicines, and improve patient safety in primary healthcare